Antibiotic resistance pattern in intensive care unit of a tertiary care teaching hospital - Bhatia, Amit; Kalra, Juhi; Kohli, Saurabh; Kakati, Barnali; Kaushik, Reshma (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Antimicrobials are a major class of drugs prescribed in Intensive Care Unit (ICU). Widespread use of empirical antibiotic therapy has facilitated the emergence of drug resistance, since empirical therapy is very often initiated at the outset, even before culture and sensitivity reports are available. The problem of drug resistance is on a rise, therefore, this study was planned to assess the drug resistance and sensitivity patterns of the blood isolates recovered from ICU. Methods: An observational- prospective study was conducted in the Tertiary care teaching hospital over a period of twelve months to assess antibiotic resistance and sensitivity pattern. A total of 104 consecutive patients receiving antibiotics in the ICU and having blood cultures with significant growth were included in the study. Blood sample was collected and after obtaining a culture growth, the identification and antimicrobial sensitivity testing was done. Results: Blood stream infection by Gram-negative bacteria (50.96%) was more common than Gram-positive bacteria (49.04%). Coagulase negative Staphylococci (CoNS) was the predominant single blood culture isolate (35.58%). Klebsiella pneumoniae (13.46%), Escherichia coli (12.50%), Acinetobacter baumannii complex (7.69%) were commonly isolated gram negative organisms. Gram positive isolates were resistant to beta lactams in maximum patients whereas Tigecycline, Linezolid, Daptomycin, Vancomycin, Nitrofurantoin and Teicoplanin were sensitive against them. Common gram negative isolates were sensitive to Colistin and Tigecycline but resistant to most of the antibiotics. Conclusions: A preponderance of gram negative bacteria over gram positive bacteria was noted with a higher degree of resistance to most of the first line antimicrobial agents.